KEDUDUKAN BENDA JAMINAN YANG DIBEBANI HAK TANGGUNGAN DAN EKSEKUSI BENDA JAMINAN DALAM HAL DEBITUR PAILIT - Ramli Siregar; Windha windha (Universitas Sumatera Utara, 2014)
When debtor is bankrupt, all of the properties of debtor are confiscated under the supervision of a Supervise Judge for the interest of creditor. The holder of guarantee right as separatist creditor can implement his right as determined in Article 1178 KUHPerdata (Civil Law) as there is not bankruptcy. But in its implementation, the execution of collateral with guarantee right when debtor is bankrupt always found any obstacles either technical or non technical obstacles. Therefore, this research aims to study how the execution of collateral when debtor is bankrupt. The problem formulation in this thesis is did the collateral can be with guarantee right, what a position of collateral with guarantee right when debtor is bankrupt and how the execution of collateral when debtor is bankrupt. The method and characteristic of study is an analysis descriptive i.e. a study that depict studied situation or event and than to analyze it based on facts such as secondary data from the primary law subject, secondary law subject and tertiary law subject. The approach method in this analysis is normative juridical by study and test the data related to the problems in execution of guarantee right. The data collecting method in this study is by literature study to collect the secondary data. The collateral can with guarantee right if the collateral is a right on land. The position of collateral with guarantee right when debtor is bankrupt is categorized as bankruptcy property. The execution of collateral when debtor is bankrupt is by title executorial and parate execution. The obstacles in the execution of collateral when debtor is bankrupt is the state auction office did not ready for the selling ob auction object of guarantee right without fiat from the Chairperson of District Court and there is debtor who has not a good will by submit a suit to the district court to expand the execution process.